The Role of E-Commerce Platforms as an Export Bridge for Culinary MSMEs: Rollin.MLG Case Study in Malang City - Agoes Windarto; Sudarmiatin; Heri Pratikno (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The internationalization of Micro, Small, and Medium Enterprises (MSMEs) through e-commerce platforms is an increasingly relevant phenomenon in the digital economy era. This study aims to analyze the role of e-commerce platforms, especially Tokopedia, Shopee, and TikTok Shop, as potential export bridges for culinary MSMEs in Indonesia, by taking a case study on rollin.mlg, a culinary MSME based in Malang City, East Java. Using a qualitative approach with an exploratory case study design, data were collected through in-depth interviews, digital platform observations, and documentation. The results of the study show that although Rollin.mlg has not exported directly, the three platforms have features that have the potential to support international market penetration. However, there are significant obstacles, including a limited product shelf life, a lack of export certification, limited production capacity, and a lack of digital export literacy. This research contributes to the development of a digital export readiness framework for Indonesian culinary MSMEs.